Evaluation of Experimental Vaccination Against Newcastle Disease and the Blood Proteinogram in Ring - Necked Pheasants (Phasianus colchicus) During Breeding Season - Schmidt, Elizabeth Moreira Dos Santos; Paulillo, Antonio Carlos; Caron, Luiz Felipe; Filho, Tobias Fernandes; Agustini, Marcelo; Ventura, Henrique Larsen Brunow; Dittrich, Rosangela Locatelli (International Journal of Poultry Science, 2008)
This study aimed to evaluate humoral immune responses and the blood proteinogram of ring-necked pheasants (Phasianus colchicus), vaccinated against Newcastle disease, during breeding season. Eighty adult birds (52 to 60 week-old) were distributed into four different groups: G1- vaccinated with NDV Ulster 2C strain, G2- vaccinated with NDV B1 strain, G3- vaccinated with NDV LaSota strain and G4-not vaccinated (control). The immune response was evaluated by the HI test. The blood proteingram of these birds also determined. The vaccination programs with Ulster 2C, B1 and LaSota strains were equally efficient to stimulate humoral immune responses. Vaccinated ring-necked females with LaSota strain showed significantly (p<0,05) alterations on serum total protein and albumin concentrations.